Analisis Pengaruh Program Bantuan Stimulan Perumahan Swadaya (BSPS) Terhadap Pertumbuhan Ekonomi - Rusdaryanti, Novieka Wahyu Putri; Marseto, Marseto; Nisa, Fauzatul Laily (Jurnal Ilmiah Wahana Pendidikan, 2023)
An assistance program from the government to the community called Self-Help Housing Stimulant Assistance (BSPS) aims to help low-income communities (MBR) as well as to improve their welfare. Funds from this program can be used to buy materials and pay the salaries of their workers. The purpose of this research is to understand how the impact of the BSPS program has on economic growth in Ponorogo Regency. The home improvement program is the general name for this BSPS program. The community can improve their welfare and housing conditions with the help of this program. Thus, the social and economic impact of this assistance program underwent many changes.